Penguatan Musik dan Tari Tradisional Aceh sebagai Upaya Pelestarian Kearifan Lokal untuk Gen- Alpha si SMPN 1 Darussalam Aceh Besar (International Forum of Researchers and Lecturers, 2025)
This study aims to strengthen Acehnese traditional music and dance as an effort to preserve local wisdom for Generation Alpha at SMPN 1 Darussalam, Aceh Besar. The background of this study the decreasing interest of students in traditional arts due to the strong influence of globalization and digital culture, particularly among Generation Alpha who grow up a technology-oriented environment. This research employed a quasi-experimental method using a one-group pretest–posttest design. The learning intervention focused on the practice of Rapai Geleng music and Ranup Lampuan traditional dance through peer tutoring and direct instruction (demonstration). The participants consisted of 35 students, including 14 male students in the Rapai Geleng class and 21 female students the Ranup Lampuan dance class. Data were collected through observation, documentation, and performance-based assessment during three instructional sessions. The findings indicate noticeable improvement in students’ practical skills, including rhythmic accuracy, coordination, group cohesiveness, movement technique, and expressive performance. In addition, students demonstrated increased motivation, confidence, and positive attitudes toward Acehnese traditional arts. The peer tutoring method enhanced collaborative learning and social interaction, while direct instruction effectively supported the mastery of procedural and psychomotor skills. The study also highlights that traditional arts learning serves a meaningful experiential medium for Generation Alpha, integrating biological potential with cultural and aesthetic experience. The results suggest that strengthening traditional music and dance education at the junior high school level plays a strategic role in preserving local wisdom, reinforcing cultural identity, and ensuring the continuity of Acehnese traditional arts in the digital era.